Microstructural understanding of the oxidation of an austenitic stainless steel in high-temperature steam through advanced characterization. (1st August 2020) - Shen, Zhao; Tweddle, David; Yu, Hongbing; He, Guanze; Varambhia, Aakash; Karamched, Phani; Hofmann, Felix; Wilkinson, Angus J.; Moody, Michael P.; Zhang, Lefu; Lozano-Perez, Sergio
Abstract: It is well-known that steels always oxidize faster in the environments containing water vapour than in dry oxygen. Due to the difficulties in obtaining necessary experimental scale of observations, the mechanisms responsible for the steam-accelerated oxidation are still unclear. Through a combination of multiscale characterization techniques, the surface oxide film formed on an Fe-17Cr-9Ni stainless steel after exposure to high-temperature steam has been studied in detail. The characterization results obtained in this study reveal that the inner oxide layer actually consists of two phases Fe-Ni austenite and FeCr2 O4 oxide, which formed due to internal oxidation. The classic internal oxidation model underestimates the thickness of the inner oxide layer by one order of magnitude. This difference can be explained by the existence of fast diffusion channels in the inner oxide layer. This study provides direct evidence of a high density of nanopores in the oxide phase of the internal oxide layer, which can act as fast-diffusion channels if interconnected, and proposes their mechanisms of formation, a consequence of water dissociation-induced protons promoting the formation, migration, and clustering of both cation and anion vacancies. Graphical abstract: Image, graphical abstract